2022
DOI: 10.3389/fonc.2022.790788
|View full text |Cite
|
Sign up to set email alerts
|

Syntenin Regulated by miR-216b Promotes Cancer Progression in Pancreatic Cancer

Abstract: Outcomes for patients with pancreatic cancer (PC) are poor; therefore, there is an urgent need to identify novel therapeutic targets involved in the progression of PC. We previously identified 161 differentially expressed proteins (DEPs) in PC. Syntenin (SDCBP) was identified as a survival-related protein through integrated, survival, and Cox analyses. High expression of SDCBP was associated with a poor prognosis in PC tissue and promoted the proliferation, migration, and invasion of PC cells, and induced epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Crucial to the occurrence and development of melanoma, SDCBP fosters PDAC growth and metastasis by obstructing TrCP-mediated proteasomal degradation [ 22 ]. Elevated levels of SDCBP correlate with an adverse prognosis in pancreatic cancer (PC), stimulate PC cell proliferation, migration, and invasiveness, and trigger epithelial-mesenchymal transition (EMT) through the activation of the PI3K/AKT pathway [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Crucial to the occurrence and development of melanoma, SDCBP fosters PDAC growth and metastasis by obstructing TrCP-mediated proteasomal degradation [ 22 ]. Elevated levels of SDCBP correlate with an adverse prognosis in pancreatic cancer (PC), stimulate PC cell proliferation, migration, and invasiveness, and trigger epithelial-mesenchymal transition (EMT) through the activation of the PI3K/AKT pathway [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, SDCBP has been identified as a major contributor to several important biological functions in cancers, including tumour invasion, metastasis, proliferation, immune evasion, tumour stemness, exosome loading and angiogenesis 11 15 17 32–34. In pancreatic cancer, the tumour promoting function of SDCBP was evaluated by IHC in 61 pancreatic cancer patients and was further validated using SDCBP-shRNA by Zu et al 18…”
Section: Discussionmentioning
confidence: 99%
“…SDCBP has been shown to be a major contributor to several important biological functions in solid tumours 10–17. Recent research by Zu et al also reported SDCBP as an oncogene in PDAC progression18; however, the function, mechanism and translation of SDCBP have not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…miR-216b is also known to reduce the expression of KRAS, thereby inhibiting the progression of pancreatic cancer and inducing apoptosis [138]. In addition, miR-216b directly targets SDCBP to inhibit its expression, thereby regulating the EMT of pancreatic cancer through the inhibition of the PI3K pathway [129].…”
Section: Pancreatic Cancermentioning
confidence: 99%